2007
DOI: 10.1080/13651820701611218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mulitprobe radiofrequency technology in a porcine model

Abstract: Multiprobe ablations using RFA are promising technologies that need further study to evaluate their clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As mentioned earlier, the safety of EB‐RFA has not yet been clearly defined, and preclinical validation of EB‐RFA is imperative. The RF energy circuit, which was made in two neighboring bipolar electrodes, delivers alternating current to produce ionic agitation in the cell, resulting in hyperthermia and coagulation necrosis in the tissue . Thus, RFA could ablate the tumor segment in the biliary tree and could be useful for assisting stenting and biliary drainage restoration in the occluded stent; whereas, the procedure has a possibility of adverse events such as perforation and bleeding due to transmural necrosis of the tumor or normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the safety of EB‐RFA has not yet been clearly defined, and preclinical validation of EB‐RFA is imperative. The RF energy circuit, which was made in two neighboring bipolar electrodes, delivers alternating current to produce ionic agitation in the cell, resulting in hyperthermia and coagulation necrosis in the tissue . Thus, RFA could ablate the tumor segment in the biliary tree and could be useful for assisting stenting and biliary drainage restoration in the occluded stent; whereas, the procedure has a possibility of adverse events such as perforation and bleeding due to transmural necrosis of the tumor or normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown different factors affecting RFA lesions using a single applicator [1,3,5,9,10,12,15,18,20,24,25]. Later studies could show the results using two applicators resulting in an improved ablation shape but without an effect on lesion size [6,7,16]. Multiple (>2) applicators have been tested to enlarge the ablation zone in a few studies.…”
Section: Discussionmentioning
confidence: 99%
“…Because RFA relies on current flow, rapid heating will cause charring of tissue and heating to temperatures > 100 °C will cause tissue water immediately adjacent to the RFA probe to boil, both of which events result in increased tissue impedance and either the overheating of the probe or the diminishing of the ablation zone 1 . Hence, RFA requires a controlled increase in temperature and prolonged ablation times (routinely > 10 min per application), despite multiple innovations intended to control probe and tissue temperature 33,34 . By contrast, the properties of MWA allow for a rapid increase in temperature throughout the microwave field without the concern of increased impedance, which, in turn, results in a much shorter application time 6 .…”
Section: Discussionmentioning
confidence: 99%